Uwagi dotyczące modelu administracji publicznej w samorządzie terytorialnym - Wojciechowski, Eugeniusz (Remarks concerning the model of public administration in the local government, 2006)
The article concerns the role of the public administration and changes occurring generally under Polish conditions. Presented concerns broad outlines of the topic and only indicate presented problems. The comments and remarks concerning the way of changes in functioning of the public administration in the local government are the subject of the paper. Despite of assimilation of the civil service territorial model to the governmental one, the first mentioned still preserves autonomy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 15-20